Effect of salicylic acid and progesterone on physiological characteristics of Kentucky bluegrass under salinity stress - Sabzmeydani, Elham; Sedaghathoor, Shahram; Hashemabadi, Davood (Revista de Ciencias Agrícolas, 2021)
Salinity is one of the most important limiting factors in plant growth. It is also a predominant constraint that impairs grass growth and quality. Plant hormones play important roles in the capability of plants to adapt to environmental stresses. Hence, the impact of two plant growth regulators (PGRs) i.e. salicylic acid (SA) and progesterone (P4) was studied on biological characteristics of Poa pratensis in saline conditions in a greenhouse experimnt. The experimental treatments were composed of salinity at four levels (0, 2, 4, and 6 dS m-1) and six levels of PGRs (control, 1 mg L-1 P4,10 mg L-1 P4, 1 mM SA, 3 mM SA, and 1 mg L-1 P4 + 1 mM SA). The results showed that leaf firing percentage was increased with the excess in salinity, but the use of SA and P4 eased the effects of salinity stress and reduced leaf firing under salinity. 6 dS m-1 and 3 mM SA salinity caused to the maximum electrolyte leakage. The highest relative water content was observed in 4 dS m-1 salinity and 1 mM SA treatment. The highest glycine betaine was related to 6 dS m-1 NaCl and no hormone application. Salinity increased total protein and catalase, and the simultaneous use of P4 and SA exhibited the highest total protein and catalase content, whilst the control plants showed the lowest ones. The application of salinity stress reduced chlorophyll content, but SA and P4 increased it. The application of the two growth regulators improved carotenoid content under salinity stress. Overall, the results showed that the application of SA and P4 improved salinity tolerance and increased pigments and antioxidant enzyme activities.